The Informational Professional and His Six Senses - Adebisi, Akanbiemu Adetola; Otuza, Chima Evans (Advances in Social Sciences Research Journal, 2017)
This paper discuses a mental perception depicting competencies of information professional. In being a relevant and effective information professional, just like a human being is endowed with senses of touch, taste, hearing, seeing so must information professionals have a sense of collaboration, creative and critical thinking, communication, culture and credibility. Information professionals need to create a positive image by building mental competencies; these competencies are what we refer to as his six senses. Information professionals are charged with the responsibility of creating, storing, organising and disseminating information. Every information professional needs information to plan, control and make decisions but having information to perform these tasks are not enough but having the sense of collaboration , to make work quicker and easier, being creative to be innovative, critical in his thinking to indicate errors and create solutions. He should also be able to communicate effectively, embrace culture and have credibility as his six senses.